Elevating the Standard of Care for Patients with Psoriasis: 'Calls to Action' from Epicensus, a Multistakeholder Pan-European Initiative - Jan Koren; Jo L. W. Lambert; Simon F. Thomsen; Helen McAteer; Gabriella Fabbrocini; Valeria Corazza; Denis Jullien; Matthias Augustin; Richard B. Warren; Menno A. de Rie; Elizabeth Lazaridou; Lluís Puig; et al. (Adis, Springer Healthcare, 2022)
Abstract Introduction Despite advances in treatment options and the management of patients with psoriasis, considerable unmet needs remain. Our objective was to identify ways to elevate the standard of care for patients with psoriasis by combining the perspectives of three important stakeholders: patients, clinicians and payors, and define 'Calls to Action' designed to achieve the identified changes. Methods Eight themes relevant to elevating the standard of care were identified from an insights-gathering questionnaire completed by all three stakeholder groups. A modified Delphi exercise gained consensus on statements informed by the insights. Statements were then used to inspire 'Calls to Action' - practical steps that could be taken to realise the desired changes and elevate the standard of care. Results In total, 18 European experts (10 dermatologists, 3 payors and 5 patient representatives) took part in the Delphi process. Consensus was reached on statements relating to all eight themes: improve healthcare systems to better support multidisciplinary team working and digital services, real-world data generation and optimal use, improve patient access, elevate quality-of-life measures as the most important outcomes, involve patients in patient-centred and personalised approaches to care, improve the relevance and reach of guidelines, education, and multistakeholder engagement. 'Calls to Action' common to all three stakeholder groups recognised the need to capitalise on the shift to digital healthcare, the need for consistent input into registries to generate real-world evidence to support guideline development, and the necessity of educating patients on the benefits of reporting outcomes to generate real-world data. The enormous quality-of-life burden and psychological impact of psoriasis, as well as the clinical needs of patients must be better understood, including by healthcare commissioners, so that funding priorities are assessed appropriately. Conclusion This unique initiative identified a practical 'Call-to-Action Framework' which, if implemented, could help improve the standard of care for patients with psoriasis. Video Abstract (MP4 44777 KB)